RELATIONSHIP BETWEEN DOMINANT PHYSICAL COMPONENTS AND ARCHERY PERFORMANCE AMONG COMPETITIVE ARCHERS AT WEST END ARCHERY ACADEMY BANDA ACEH - muhammad heriansyah; Teta Arum Darandi Darandi; Bungsu Amelia Sofya Sofya; Santi Sundari (Journal of Health and Recreation Physical Education (JHRPE), 2026)
This study aimed to analyze the relationship between dominant physical components and archery performance among competitive archers at West End Archery Academy Banda Aceh in 2026. This research employed a quantitative approach with a correlational method. The sample consisted of 12 athletes selected using a total sampling technique. The physical condition variables examined included arm muscle strength, muscular endurance, and body balance, while archery performance was measured using athletes’ shooting scores. The research instruments included the push-up test, plank test, stork stand balance test, and shooting score test. Data were analyzed using descriptive statistics, Shapiro-Wilk normality test, and Pearson Product Moment correlation test with the assistance of SPSS software. The results showed that all physical condition components had a positive and significant relationship with archery performance. Body balance demonstrated the strongest correlation with shooting score (r = 0.914), followed by arm muscle strength (r = 0.876) and muscular endurance (r = 0.842). These findings indicate that physical condition plays an important role in improving postural stability, movement consistency, and shooting accuracy among archers. conclusion, dominant physical components significantly contribute to archery performance among competitive archers. Therefore, specific and sport science-based physical training programs should be implemented to improve athletes’ achievements in archery.